2007
DOI: 10.1038/nrd2217
|View full text |Cite
|
Sign up to set email alerts
|

How can drug discovery for psychiatric disorders be improved?

Abstract: Psychiatric disorders such as depression, anxiety and schizophrenia are leading causes of disability worldwide, and have a huge societal impact. However, despite the clear need for better therapies, and major advances in the understanding of the molecular basis of these disorders in recent years, efforts to discover and develop new drugs for neuropsychiatric disorders, particularly those that might revolutionize disease treatment, have been relatively unsuccessful. A multidisciplinary approach will be crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
154
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(164 citation statements)
references
References 70 publications
6
154
1
1
Order By: Relevance
“…24,25 This finding was reinforced by Agid et al, who showed different pathways for BDNF/TrkB (tyrosine-related kinase B) and IGF-1/IGF-1R (insulin-like growth factor 1 receptor) in the neurotransmitter systems involved in schizophrenia, culminating in benefits in neuroplasticity. 26 IGFBP-3, the most prevalent binding protein, carries most of the serum IGFs, regulating their actions and controlling their distribution to target tissues. The IGF-IGFBP-3 axis is involved in the pathogenesis of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 This finding was reinforced by Agid et al, who showed different pathways for BDNF/TrkB (tyrosine-related kinase B) and IGF-1/IGF-1R (insulin-like growth factor 1 receptor) in the neurotransmitter systems involved in schizophrenia, culminating in benefits in neuroplasticity. 26 IGFBP-3, the most prevalent binding protein, carries most of the serum IGFs, regulating their actions and controlling their distribution to target tissues. The IGF-IGFBP-3 axis is involved in the pathogenesis of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Animal (experimental) models have long been used in translational neuroscience to study brain mechanisms and their effects on behavior. 3,4 Environmental, genetic, and pharmacological manipulations are widely used to probe brain mechanisms and circuits in various animal models.…”
mentioning
confidence: 99%
“…The most widely used antidepressants, the serotonin selective reuptake inhibitors (SSRIs), are administered to depressive patients with an underlying dysfunction in the serotonin (5-HT) system, or in other neurotransmitter systems or circuits that are modulated by 5-HT (Gingrich & Hen, 2001;Hen, 1996;Nestler et al, 2002). Many current and potential therapies for depression are focused on either directly or indirectly modulating the serotonergic system (Agid et al, 2007). Recently, increasing evidence demonstrated that the levels of monoamine neurotransmitters were decreased by UCMS and reversed by the administration of antidepressants (Bekris et al, 2005;Savegnago et al, 2007).…”
Section: Introductionmentioning
confidence: 99%